Alleviation of LED nonlinearity impact in visible light communication using companding and predistortion. Issue 7 (1st April 2019) - Lu, Huimin; Jin, Jianli; Wang, Jianping
Abstract : In order to suppress the nonlinearity impact of light‐emitting diodes (LEDs) on the performance of visible light communication (VLC), the combined method including companding and predistortion was proposed in this work. The modified companding and predistortion based on the LED characteristic analysis were used corresponding to the output current ‐input voltage (I‐V) and light output‐injected current (L‐I) nonlinearity, respectively. Using the combined method, the performances of the DC‐biased optical orthogonal frequency division multiplexing (DCO‐OFDM) VLC system were analysed. It is demonstrated that the non‐linear distortion of OFDM transmitted signal is alleviated, thus the received signal quality is increased. As a result, the bit error rate (BER) performance of VLC system is improved obviously by using the combined method of companding and predistortion. Furthermore, the applicability of this combined method is also verified by analysing the nonlinearity suppression of the VLC system using different LED. The results reveal that both the impact from LED's I‐V and L‐I nonlinearity can be alleviated using the proposed method combining from companding and predistortion for DCO‐OFDM VLC system.